Evaluation of Lipid-Based Coatings on Postharvest Quality of Tomatoes during Ambient Storage (Journal of Tropical Resources and Sustainable Science (JTRSS), 2026)
Tomatoes (Solanum lycopersicum) are susceptible to postharvest losses due to metabolic processes, physical injuries, and microbial spoilage. Edible coatings are a promising strategy to extend the shelf life of fresh fruits, including tomatoes, by providing a protective layer that controls the transfer of gases, moisture, aromas and volatile substances during storage. Thus, this study evaluated the effectiveness of lipid-based composite edible coatings in maintaining the postharvest quality of tomatoes stored at ambient conditions (24–26 °C, 65–75 % RH). Three coating emulsions were formulated in this study: F1 = coconut oil-lemongrass essential oil (CL), F2 = beeswax-coconut oil-lemongrass essential oil (BCL), and F3 = carboxymethylcellulose (CMC)-coconut oil-lemongrass essential oil (CCL). These coatings were applied to tomatoes at the turning stage and compared with uncoated samples over a 24-day period. Quality parameters, including weight loss, visual appearance, firmness, total soluble solids (TSS), and surface morphology, were evaluated at the end of the experiment. All coatings minimised moisture loss compared to the control, with F2 (BCL) showing the greatest reduction. Nonetheless, F3 (CCL) outperformed other coatings in preserving tomato firmness (525.07 ± 103.09 g) and TSS (4.50 ± 0.50 °Brix ), indicating enhanced control of the respiration and ripening. Microscopic analysis further revealed that F3 (CCL) formed a smooth, homogenous coating layer, with improved barrier features and no adverse sensory effects. Conversely, F2 (BCL) exhibited uneven coating distribution due to beeswax crystallisation, causing undesirable surface deposits and decreased firmness retention. These findings highlighted the potential of lipid-polysaccharide composite, particularly with CMC inclusion, to prolong the postharvest shelf life of tomatoes by reducing weight loss and retaining firmness and TSS content. Component compatibility is also crucial for structural integrity, functional properties, and consumer acceptability in edible coating applications.
Keywords: physicochemical properties; microscopy; edible coating; tomato preservation